Deciphering the Palaeocene-Eocene thermal maximum by Granger causality test - Zeyang Liu; Xiehua Ji; Wenyan Luo; Yujie Hu; Haoran Liu (Geosystems and Geoenvironment, 2023)
The Palaeocene-Eocene thermal maximum is a global warming period (∼56 Ma), which is marked by a sharp negative carbon isotope excursion (CIE) that caused by the injection of massive isotopically-light carbon into the ocean-atmosphere. It is generally considered that the carbon injection caused global warming. However, several studies have suggested that warming and environmental perturbations precede the onset of the CIE. Here we present Granger test to investigate the detailed mechanisms of this event. We show a shift from climate-warming driving carbon-emission scenario to a scheme in which carbon-injection causing global-warming during the CIE. The initial carbon emission might be from methane hydrates dissociation and/or permafrost thawing, possibly linked with astronomical paced warming. This change of causal direction may result from the warming feedback of the emitted carbon and additional carbon from other sources, such as volcanism, bolide impact, oxidation of marine organic matter, and wildfires burning peatlands.